Sirolimus treatment for intractable lymphatic anomalies: an open-label, single-arm, multicenter, prospective trial - Ozeki, Michio; Endo, Saori; Yasue, Shiho; Nozawa, Akifumi; Asada, Ryuta; Saito, Akiko M.; Hashimoto, Hiroya; Fujimura, Takumi; Yamada, Yohei; Kuroda, Tatsuo; Ueno, Shigeru; Watanabe, Shoji; et al. (Frontiers in Medicine, 2024)
Introduction Intractable lymphatic anomalies (LAs) include cystic lymphatic malformation (LM; macrocystic, microcystic, or mixed), generalized lymphatic anomaly, and Gorham-Stout disease. LAs can present with severe symptoms and poor prognosis. Thus, prospective studies for treatments are warranted. We conducted a prospective clinical trial of sirolimus for intractable LAs.This was an open-label, single-arm, multicenter, prospective trial involving five institutions in Japan. All patients with LAs received oral sirolimus once daily, and the dose was adjusted to ensure that the trough concentration remained within 5-15 ng/mL. We prospectively assessed the drug response (response rate for radiological volumetric change in target lesion), performance state, change in respiratory function, visceral impairment (pleural effusion, ascites, bleeding, pain), laboratory examination data, quality of life (QOL), and safety at 12, 24, and 52 weeks of administration.Results: Eleven patients with LAs (9 generalized lymphatic anomaly, 1 cystic LM, 1 Gorham-Stout disease) were treated with sirolimus, of whom 6 (54.5%; 95% confidence interval: 23.4%-83.3%) demonstrated a partial response on radiological examination at 52 weeks of administration. No patients achieved a complete response. At 12 and 24 weeks of administration, 8 patients (72.7%) already showed a partial response. However, patients with stable disease showed minor or no reduction after 12 weeks. Adverse events, such as stomatitis, acneiform dermatitis, diarrhea, and fever, were common with sirolimus. Sirolimus was safe and tolerable.Conclusions: Sirolimus can reduce the lymphatic tissue volume in LAs and may lead to improvements in clinical symptoms and QOL.